Temperate Streptococcus thermophilus phages expressing superinfection exclusion proteins of the Ltp type - Ali, Yahya; Koberg, Sabrina; Heßner, Stefanie; Sun, Xingmin; Rabe, Björn; Back, Angela; Neve, Horst; Heller, Knut J. (Frontiers in Microbiology, 2014)
Lipoprotein Ltp encoded by temperate Streptococcus thermophilus phage TP-J34 is the prototype of the wide-spread family of host cell surface-exposed lipoproteins involved in superinfection exclusion. When screening for other S. thermophilus phages expressing this type of lipoprotein, three temperate phages - TP-EW, TP-DSM20617 and TP-778 - were isolated. In this communication we present the total nucleotide sequences of TP-J34 and TP-778L. For TP-EW, a phage almost identical to TP-J34, besides the ltp gene only the two regions of deviation from TP-J34 DNA were analyzed: the gene encoding the tail protein causing an assembly defect in TP-J34 and the gene encoding the lysin, which in TP-EW contains an intron. For TP-DSM20617 only the sequence of the lysogeny module containing the ltp gene was determined. The region showed high homology to the same region of TP-778. For TP-778 we could show that absence of the attR region resulted in aberrant excision of phage DNA. The amino acid sequence of mature LtpTP-EW was shown to be identical to that of mature LtpTP-J34, whereas the amino acid sequence of mature LtpTP-778 was shown to differ from mature LtpTP-J34 in eight amino acid positions. LtpTP-DSM20617 was shown to differ from LtpTP-778 in just one amino acid position. In contrast to LtpTP-J34, LtpTP-778 did not affect infection of lactococcal phage P008 instead increased activity against phage P001 was noticed.